Modification method for enhancing loading performance of medical stone fungicide
By alkali activation and surface modification of Mafanshi, the problem of low load efficiency of Mafanshi fungus agents is solved, which significantly improves its functional performance in water body repair and enhances the load efficiency and stability of plant fungus agents.
Patent Information
- Application Number
- CN202411915929.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, the load efficiency of the Maifanite fungus agent is low, which limits its function in water body restoration, especially in the field of submerged plant restoration.
Through alkali activation treatment and surface modification treatment, the surfactivity and selectivity of Maifanshi are improved and its loading efficiency on plant bacterial promoters is enhanced. Specific steps include: alkali activation treatment, surface modification treatment and bacterial agent loading treatment.
It significantly improves the adsorption capacity and load stability of Maifanshi as a fungic agent carrier, enhances its activity and stability in water and soil, promotes the ecological restoration process, and reduces production costs.
Smart Images

Figure CN119614206A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water environment treatment and ecological restoration, and specifically belongs to a modification method for strengthening the loading performance of medical stone microbial agent. Background Art
[0002] With the continuous development of water environment management, the goal of water body restoration has gradually shifted from simple pollutant removal to a comprehensive requirement that emphasizes both pollution prevention and ecological restoration. At present, water body restoration should not only focus on the effective removal of pollutants, but also focus on promoting the recovery of aquatic plants and microbial communities. This shift has promoted the widespread application of multifunctional materials in water body management. In order to meet this new demand, the development of water treatment materials with multiple functions has become an important research direction. These new materials can not only efficiently remove pollutants from water, but also restore and improve the ecological environment of water bodies, helping to rebuild aquatic habitats.
[0003] As a natural mineral material, medical stone has been widely used in the field of water restoration due to its excellent physical and chemical properties. Medical stone has a large specific surface area and porous structure, which enables it to efficiently remove metal ions, eutrophic substances and harmful pollutants in water through mechanisms such as physical adsorption, chemical reaction and ion exchange. In addition, as a natural mineral, medical stone is not only eco-friendly, but its mineral components help improve water quality, promote the growth of aquatic plants, and provide a better environment for aquatic ecosystems. These unique advantages make medical stone show a wide range of application prospects in water pollution control and ecological restoration.
[0004] In addition to its basic pollutant adsorption function, the ecological affinity of medical stone also provides good conditions for it to be used as a carrier to load plant growth-promoting bacteria. Therefore, in recent years, related research has been derived on using medical stone as a carrier to load bacteria to form plant growth-promoting agents. Medical stone-based plant growth-promoting agents are not only expected to improve the overall effect of water pollution control, but also provide new ideas and technical paths for the restoration of ecosystems.
[0005] Although there have been studies that have improved the adsorption properties of medical stone through inorganic or organic modification methods, such as the Chinese patent application with application number 202211134505.8, which discloses a medical stone-based microbial compound fertilizer and a preparation method thereof, wherein the activated modified medical stone is obtained by ball milling and microwave treatment of medical stone, and then adding an alkaline activator for calcination; such as the Chinese patent application with application number 202410050089.6, which discloses a modified medical stone passivation material and a preparation method and application thereof, the invention modifies the medical stone powder by a hydrochloric acid solution, removes impurities in the pores of the natural medical stone, and improves the solidification effect on microorganisms and the adsorption capacity of heavy metals in the soil.
[0006] However, when dealing with more complex water treatment needs, especially in the field of submerged plant restoration, there is still much room for improvement. In particular, there are relatively few studies on the modification of the surface properties of medical stone, and after surface modification, the bacterial agent loading performance of medical stone has significant potential for improvement. At present, most of the existing modification technologies focus on increasing the specific surface area of medical stone to improve its adsorption performance. However, improving its surface activity and selectivity to enhance the efficiency of bacterial agent loading, especially the efficiency of loading plant growth-promoting agents, is still a technical problem that needs to be solved urgently.
[0007] Therefore, in view of the above technical problems, it is particularly important to develop a modification method that can effectively enhance the loading performance of medical stone microbial agents. Through surface modification technology, not only can the surface activity and selectivity of medical stone be improved, but also its loading efficiency for plant growth-promoting microbial agents can be significantly improved, thereby enhancing its performance in complex water environments and making it a more effective ecological restoration material. Summary of the invention
[0008] The present invention aims to provide a modification method for enhancing the loading performance of medical stone microbial agent, so as to solve the problem that the loading efficiency of natural medical stone microbial agent is low and the function of medical stone in water body restoration is limited.
[0009] The modification method for strengthening the loading performance of medical stone microbial agent comprises the following steps: S1, alkali activation treatment: soak the medical stone in an alkaline solution for alkali activation treatment, wash it after soaking until the pH of the washing solution is 6.5-7.5, and obtain activated medical stone after drying; S2, surface modification treatment: dispersing a surface modifier in a solvent to obtain a surface modifier solution, immersing the activated medical stone obtained in step S1 in the surface modifier solution, adding an acid catalyst, reacting under stirring conditions, taking out the reacted medical stone after the reaction is completed, washing and drying, and obtaining medical stone with enhanced load performance; S3. Bacterial agent loading treatment: dilute the plant growth-promoting bacteria in the logarithmic growth phase with sterile physiological saline to obtain a plant growth-promoting bacteria dilution solution, add the medical stone with enhanced loading performance prepared in step S2, place it in a constant temperature shaking incubator for adsorption culture, and separate the medical stone bacterial agent after the adsorption culture is completed.
[0010] Preferably, the particle size of the medical stone is 40-100 meshes, which can not only ensure that it has sufficient specific surface area during the modification process, but also improve the uniformity of the particles, which is convenient for processing in subsequent steps.
[0011] Preferably, in step S1, ultrapure water is used to clean and dry the medical stone before the alkali activation treatment. Cleaning can remove surface impurities and floating dust to ensure surface cleanliness and reduce interference from impurities in subsequent modification processes, and drying is to ensure stability of subsequent treatments.
[0012] More preferably, the drying temperature is 80-120° C. and the drying time is 6-10 h, until a constant weight state is reached.
[0013] Preferably, the alkaline solution in step S1 includes sodium hydroxide solution or potassium hydroxide solution. Alkaline activation not only removes surface impurities, but also effectively enhances the surface electronegativity and adsorption performance of the material.
[0014] Preferably, the concentration of the alkaline solution in step S1 is 0.5-2 mol / L.
[0015] Preferably, in step S1, the mass ratio of medical stone to alkaline solution is 1:3-1:6.
[0016] Preferably, in step S1, the temperature of the alkali activation treatment is 25-50°C and the duration is 2-6 hours.
[0017] Preferably, in step S1, the alkali activation treatment is carried out under stirring at a rotation speed of 300-600 rpm.
[0018] Preferably, in step S2, the surface modifier comprises organosilane.
[0019] More preferably, the organosilane surface modifier includes tetraethyl orthosilicate, methyltrimethoxysilane or methyltriethoxysilane.
[0020] Preferably, in step S2, the solvent includes methanol, ethanol or isopropanol.
[0021] Preferably, in step S2, the concentration of the surface modifier in the surface modifier solution is 2.5wt%~7.5wt%.
[0022] Preferably, in step S2, the mass ratio of the activated medical stone to the surface modifier solution is 1:10-1:20.
[0023] Preferably, in step S2, the acid catalyst includes hydrochloric acid, nitric acid or glacial acetic acid.
[0024] Preferably, in step S2, the reaction temperature is 50-90°C and the reaction time is 2-4 hours. The reaction temperature and reaction time depend on the properties of the selected surface modifier and the reaction conditions.
[0025] Preferably, in step S2, the drying temperature is 60-80° C. to avoid decomposition of the functional groups of the modifier.
[0026] Preferably, in step S3, the plant growth-promoting bacteria include Pseudomonas putida, Brevibacillus psychrophilus or Bacillus simplex.
[0027] Preferably, in step S3, the concentration of the plant growth-promoting bacteria after dilution is 1×10 6 ~1000×10 6 CFU / mL.
[0028] Preferably, in step S3, the mass ratio of the medical stone with enhanced loading performance to the plant growth-promoting bacteria dilution is 1:5-1:10.
[0029] Preferably, in step S3, the constant temperature of the adsorption culture is 25-35°C, the rotation speed is 200-500 rpm, and the duration is 12-24 h.
[0030] A medical stone inoculant is prepared by the modification method for enhancing the loading performance of the medical stone inoculant.
[0031] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention significantly improves the adsorption capacity and loading stability of medical stone as a bacterial agent carrier by precisely modifying the surface of medical stone; by optimizing the surface modification process (such as drying temperature, modifier concentration, reaction time and other key parameters), the uniform attachment and stable existence of the bacterial agent on the surface of medical stone are ensured, thereby enhancing its application effect as plant growth-promoting particles.
[0032] (2) The present invention uses medical stone as a carrier and combines it with plant growth-promoting bacteria to effectively improve its activity and stability in water and soil, thereby accelerating the ecological restoration process. Medical stone after surface modification can better adsorb and release bacteria, optimize biodegradation and purification processes, and has a significant promoting effect on environmental restoration.
[0033] (3) The present invention uses medical stone, a cheap and abundant natural mineral material, combined with a simple modification and loading process, which greatly reduces the production cost and improves the economic efficiency of the technology. In addition, the wide availability and efficient use of medical stone make this technology have broad application prospects in large-scale ecological restoration projects, meeting the needs of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The infrared spectra of medical stone before and after surface modification.
[0035] Figure 2This is the SEM image of medical stone after surface modification with ethyl orthosilicate.
[0036] Figure 3 This is the SEM image of medical stone after surface modification with methyltrimethoxysilane.
[0037] Figure 4 These are SEM images of the bacterial agent loading on medical stone before and after surface modification. DETAILED DESCRIPTION
[0038] The technical scheme of the present invention is further described below by way of examples. The raw materials used in the examples can be purchased from the market or prepared by conventional methods.
[0039] Example 1 A modification method for strengthening the loading performance of medical stone microbial agent comprises the following steps: S1. Alkali activation treatment: S101, washing the natural medical stone with ultrapure water for multiple times to remove surface impurities and dust, placing it in a drying oven at 80°C after washing, and drying it for 6 hours until the medical stone reaches a constant weight; S102, the dried medical stone is crushed into 40 meshes by mechanical crushing process to ensure that the specific surface area is appropriate, and then sieved to ensure that the particle size is uniform; S103, soaking the crushed medical stone in 1 mol / L sodium hydroxide solution, reacting at a mass ratio of 1:3, with a soaking temperature of 30 °C, a time of 3 h, and a stirring speed of 500 rpm; during the treatment process, surface impurities are removed and adsorption sites are increased; S104, after the reaction is completed, the sample is repeatedly washed until the pH value is close to 7, and finally dried at 80 ° C for 6 h, and the obtained activated medical stone is stored for later use; S2. Surface modification: S201, selecting tetraethyl orthosilicate as a surface modifier, dissolving it in ethanol, and fully dispersing it by magnetic stirring to form a surface modifier solution with a concentration of 5%; S202, adding the activated medical stone prepared in step S104 to the surface modifier solution prepared in step S201, ensuring that the activated medical stone particles are completely immersed and evenly distributed, and the mass ratio of the activated medical stone to the surface modifier solution is 1:10; S203, adding an appropriate amount of hydrochloric acid as an acid catalyst, reacting at a temperature of 50°C for 2 hours, ensuring that the particle surface of each activated medical stone is fully in contact with the modifier; 204. After the reaction is completed, the surface-modified medical stone is separated from the reaction solution by suction filtration to remove unreacted substances, and the surface-modified medical stone is repeatedly washed with anhydrous ethanol to remove impurities remaining on the surface; 205. Dry the surface-modified medical stone obtained in step S204 at a temperature of 60° C. to ensure that the surface-modified medical stone is stable, and store it in a dryer for subsequent use; S3, Bacterial agent loading treatment: S301, Pseudomonas putida, Brevibacterium frostii and Bacillus simplex were cultured in a ratio of 1:2:2 until the logarithmic growth phase, using LB medium, the shaking speed was 200 rpm, the culture time was 12 h, and the cultured bacteria were diluted with sterile saline to a concentration of 1×10 6 CFU / mL; S302, mixing the surface-modified medical stone obtained in step S205 with the diluted bacterial solution in step S301 at a mass ratio of 1:5, placing in a constant temperature shaker at 30°C, shaking at 200 rpm, and the reaction time is 12 h to ensure that the bacterial agent is evenly attached to the surface of the medical stone; S303, after the adsorption process is completed, the modified medical stone and the residual bacterial solution are separated by centrifugation; the bacterial agent attached to the medical stone after centrifugation forms stable plant growth-promoting particles to obtain the medical stone bacterial agent.
[0040] like Figure 1 As shown in the figure, the characteristic peaks of medical stone changed significantly after surface modification, indicating that ethyl orthosilicate was successfully combined with the surface of medical stone through covalent bonds.
[0041] like Figure 2 As shown in the figure, through scanning electron microscopy (SEM) observation, the surface structure of medical stone after surface modification is more uniform and dense, and presents a more regular rough structure, which is conducive to the adhesion of bacterial agents and improves their loading performance.
[0042] Example 2 A modification method for strengthening the loading performance of medical stone microbial agent comprises the following steps: S1. Alkali activation treatment: S101, washing the natural medical stone with ultrapure water for multiple times to remove surface impurities and dust, placing it in a drying oven at 80°C after washing, and drying it for 6 hours until the medical stone reaches a constant weight; S102, the dried medical stone is crushed into 40 meshes by mechanical crushing process to ensure that the specific surface area is appropriate, and then sieved to ensure that the particle size is uniform; S103, soaking the crushed medical stone in 1 mol / L sodium hydroxide solution, reacting at a mass ratio of 1:3, with a soaking temperature of 30 °C, a time of 3 h, and a stirring speed of 500 rpm; during the treatment process, surface impurities are removed and adsorption sites are increased; S104, after the reaction is completed, the sample is repeatedly washed until the pH value is close to 7, and finally dried at 80 ° C for 6 h to obtain activated medical stone, which is stored for later use; S2. Surface modification: S201, selecting methyltrimethoxysilane as a surface modifier, dissolving it in methanol, and forming a surface modifier solution with a concentration of 7.5% through ultrasonic treatment; S202, adding the activated medical stone obtained in step S104 into the modified solution, ensuring that the medical stone particles are completely immersed and evenly distributed, and the mass ratio of the activated medical stone to the surface modifier solution is 1:15; S203, adding nitric acid as an acid catalyst, reacting at a temperature of 70°C for 3 h to ensure that the surface modifier fully reacts with the surface of the medical stone; S204, after the reaction is completed, the surface-modified medical stone is separated from the reaction solution by suction filtration to remove unreacted substances, and then the surface-modified medical stone is repeatedly washed with anhydrous ethanol to remove impurities remaining on the surface; S205, drying the surface-modified medical stone obtained in step S204 at a temperature of 70° C. and storing it in a dryer for subsequent use; S3, Bacterial agent loading treatment: S301, Pseudomonas putida, Brevibacterium frostii and Bacillus simplex were cultured in LB medium at a ratio of 1:3:6 until the logarithmic growth phase, with a shaking speed of 300 rpm and a culture time of 18 h. The cultured bacteria were diluted with sterile saline to a concentration of 10×10 6 CFU / mL; S302, mixing the surface-modified medical stone obtained in step S205 with the diluted bacterial solution in step S301 at a mass ratio of 1:8, placing in a constant temperature shaker at 32.5°C, and reacting for 18 hours to ensure uniform attachment of the bacterial agent; S303, after the adsorption process is completed, the modified medical stone and the residual bacterial solution are separated by centrifugation, and finally stable particles attached with the plant growth-promoting bacterial agent are obtained to prepare the medical stone bacterial agent.
[0043] like Figure 3As shown in the figure, the surface structure of the modified medical stone is more uniform and has obvious microscopic pores under scanning electron microscopy (SEM). Specifically, the average diameter of the surface pores is 50-100 μm. Compared with the unmodified medical stone (pore diameter is about 20-40 μm), the pores of the modified medical stone are more developed, which helps to increase the attachment area of the bacterial agent.
[0044] Example 3 A modification method for strengthening the loading performance of medical stone microbial agent comprises the following steps: S1. Alkali activation treatment: S101, wash the natural medical stone with ultrapure water for several times to ensure the surface is clean, and then dry it at 100 °C for 8 h to ensure that the surface moisture is completely removed; S102, the dried medical stone is mechanically crushed to 60 mesh, and the particle size is ensured to be uniform by sieving; S103, soaking the crushed medical stone in 1.5 mol / L sodium hydroxide solution at a mass ratio of 1:4, at a soaking temperature of 40°C, for 4 h, and at a stirring speed of 400 rpm to enhance surface activity; S104, after the reaction is completed, remove impurities by washing for multiple times, wash until the pH value is close to 7, and then dry at 100 ° C for 8 h to obtain activated medical stone, which is stored for later use; S2. Surface modification: S201, selecting methyltriethoxysilane as a surface modifier, and dissolving it in isopropanol, and forming a surface modifier solution with a concentration of 2.5% by magnetic stirring or ultrasonic treatment; S202, adding the activated medical stone obtained in step S104 to the surface modifier solution in step S201, ensuring that the medical stone particles are completely immersed and evenly distributed, and the mass ratio of the activated medical stone to the surface modifier solution is 1:20; S203, adding glacial acetic acid as an acid catalyst to react at a temperature of 90°C for 4 h to ensure that the modifier fully reacts with the surface of the medical stone; S204, after the reaction is completed, the surface-modified medical stone is separated from the reaction solution by suction filtration to remove unreacted substances, and then the surface-modified medical stone is repeatedly washed with anhydrous ethanol to remove impurities remaining on the surface; S205: drying the medical stone obtained in step S204 at a temperature of 80° C. to ensure that the medical stone after surface modification is stable, and storing it in a dryer for subsequent use; S3, Bacterial agent loading treatment: S301, select Pseudomonas putida, Brevibacterium frostii and Bacillus simplex in a ratio of 1:5:5 and culture them in LB medium until the logarithmic growth phase, the shaking speed is 500 rpm, the culture time is 24 h, and the cultured bacteria are diluted with sterile saline to a concentration of 1000×10 6 CFU / mL.
[0045] S302, mixing the surface-modified medical stone obtained in step S205 with the diluted bacterial solution in step S301 at a mass ratio of 1:10, placing in a 27°C constant temperature shaker, and reacting for 24 hours to ensure that the bacterial agent can be evenly attached; S303, after the adsorption process is completed, the modified medical stone and the residual bacterial solution are separated by centrifugation, and finally stable particles attached with the plant growth-promoting bacterial agent are obtained to prepare the medical stone bacterial agent.
[0046] like Figure 4 As shown in the figure, the loading capacity of microbial agent on the surface-modified medical stone has been significantly improved by scanning electron microscopy (SEM). In addition, in the microbial agent loading test, the modified medical stone showed a higher adsorption capacity and stronger stability, indicating that its loading performance as a microbial agent carrier has been significantly improved.
[0047] Testing and analysis (1) Test of bacterial agent loading When determining the amount of bacterial agent loaded, the adsorption method is used to calculate the amount of bacterial agent loaded per gram of medical stone. First, the modified medical stone is loaded with bacterial agent (see the specific embodiment for relevant parameters), and the unadsorbed bacterial agent is removed by centrifugation (centrifugal speed is 5000rpm, time is 10 min). By measuring the concentration of unadsorbed bacterial agent in the solution and combining the initial mass of medical stone, the amount of bacterial agent loaded per gram of medical stone is calculated, and the results are shown in Table 1.
[0048] Table 1 Bacteria dosage table of different medical stones
[0049] (2) Stability test The stability test mainly examines the stability of the loaded bacterial agent, that is, whether the survival rate of the bacterial agent and the loading effect decline within a certain period of time. The medical stone samples loaded with bacterial agents are immersed in buffer solutions of different pH values (pH values are 3, 5, 7, and 9), and the concentration of the bacterial agent in the solution is periodically measured to determine the stability of the bacterial agent. The pH range of the test is 3 to 9, and the test duration is 1 month. The colony count in the bacterial agent solution is determined by spectroscopy every month, and then the survival rate is calculated. The results are shown in Table 2.
[0050] Table 2 Determination of colony survival rate in bacterial solution
[0051] (3) Long-term effectiveness test The long-term test is used to evaluate the sustained release performance of the microbial agent on medical stone, that is, whether the microbial agent can continue to effectively play its role over a period of time. The modified medical stone was immersed in a simulated environmental liquid, which was a 0.1 M phosphate buffer with a pH of 7.4. The concentration of the microbial agent was measured every 24 hours at a temperature of 25 ° C. The test was continued for 7 days to determine its 7-day release amount. The test results are shown in Table 3.
[0052] Table 3 Release rate of samples in 7 days
[0053] In the bacterial agent loading test, the modified medical stone showed a higher bacterial agent adsorption capacity and stronger stability, indicating that its loading performance as a bacterial agent carrier has been significantly improved.
[0054] It should be understood that the above embodiments are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of the present application.
Claims
1. A modification method for enhancing the loading performance of medical stone microbial agent, characterized in that: The following steps are involved: S1, alkali activation treatment: soaking the medical stone in an alkaline solution for alkali activation treatment, washing it after soaking until the pH of the washing solution is 6.5-7.5, and drying it to obtain activated medical stone; S2, surface modification treatment: dispersing a surface modifier in a solvent to prepare a surface modifier solution, immersing the activated medical stone prepared in step S1 in the surface modifier solution, adding an acid catalyst and an appropriate amount of water, and reacting under stirring. After the reaction is completed, the reacted medical stone is taken out and washed and dried to obtain medical stone with enhanced load performance; S3. Bacterial agent loading treatment: dilute the plant growth-promoting bacteria in the logarithmic growth phase with sterile physiological saline to prepare a plant growth-promoting bacteria dilution solution, add the medical stone with enhanced loading performance prepared in step S2, place it in a constant temperature shaker for adsorption culture, and separate the medical stone bacterial agent after the adsorption culture is completed.
2. The method for modifying the loading performance of the medical stone microbial agent according to claim 1, wherein: The particle size of the medical stone described in step S1 is 40-100 meshes.
3. The method for modifying the loading performance of the medical stone microbial agent according to claim 1, wherein: In step S1, before the alkali activation treatment, the medical stone is cleaned and dried using ultrapure water.
4. The method for modifying the loading performance of medical stone bacteria agent according to claim 1, wherein The alkaline solution described in step S1 includes sodium hydroxide solution or potassium hydroxide solution; the concentration of the alkaline solution described in step S1 is 0.5~2 mol / L; in step S1, the mass ratio of medical stone to alkaline solution is 1:3~1:6; in step S1, the temperature of the alkaline activation treatment is 25~50°C, and the duration is 2~6 hours; in step S1, the alkaline activation treatment is carried out under stirring at a rotation speed of 300~600 rpm.
5. The method for modifying the loading performance of medical stone microbial agent according to claim 1, wherein: In step S2, the surface modifier includes organosilane.
6. The method for modifying the loading performance of medical stone bacteria agent according to claim 5, wherein: The organosilane includes ethyl orthosilicate, methyltrimethoxysilane or methyltriethoxysilane.
7. The method for modifying the loading performance of medical stone bacteria agent according to claim 1, wherein: In step S2, the concentration of the surface modifier in the surface modifier solution is 2.5% to 7.5%; in step S2, the mass ratio of the activated medical stone to the surface modifier solution is 1:10 to 1:
20.
8. The method for modifying the loading performance of medical stone bacteria agent according to claim 1, wherein In step S2, the acid catalyst includes hydrochloric acid, nitric acid or glacial acetic acid; in step S2, the reaction temperature is 50-90°C and the reaction time is 2-4 hours; in step S2, the drying temperature is 60-80°C.
9. The method for modifying the loading performance of medical stone bacteria agent according to claim 1, wherein In step S3, the plant growth-promoting bacteria include Pseudomonas putida, Brevibacterium frostii or Bacillus simplex; in step S3, the concentration of the plant growth-promoting bacteria after dilution is 1×10 6 ~1000×10 6 CFU / mL; in step S3, the mass ratio of the medical stone with enhanced loading performance to the plant growth-promoting bacteria dilution is 1:5~1:10; in step S3, the constant temperature of the adsorption culture is 25~35 ℃, the rotation speed is 200~500 rpm, and the duration is 12~24 h.
10. A medical stone bacterial agent, characterized in that The medical stone inoculant is prepared by a method for enhancing the loading performance of the medical stone inoculant described in any one of claims 1 to 9.
Citation Information
Patent Citations
Medical stone-based microbial compound fertilizer and preparation method thereof
CN115353435A
Modified medical stone passivation material as well as preparation method and application thereof
CN117903805A